CRITICAL THINKING FOR ACCOUNTING STUDENTS USING PROBLEM BASED LEARNING INTEGRATING WITH ICT MEDIA (JURNAL ECONOMICA : Research of Economic And Economic Education, 2020)
Critical thinking ability is one of skill that student must be have so student get used to analyze and solving the problem in the world of work, especially the world of accounting. This study aims to determine the improvement of students' critical thinking skills by using problem based learning model integrating ICT media. The sample technique used cluster random sampling in Boyolali, Indonesia. This research uses an action research approach. Data collection in this research using observation technique, interview, and documentation. Validity of the data used triangulation of sources, data, and methods. The result of this research by using problem based learning model with ICT media shows that there is an increase of critical thinking ability of accounting students which consists of five aspects of critical thinking that are aspects of ability to formulate questions, give argument, collect and arrange information, analyze problem, and decision making and making conclusion